Solutions of einstein's field equations for charged static fluid spheres - Singh T.; Singh G.P.; Helmi A.M. (My University, 2025)
In this paper the authors have extended Bayin's (1978) work to the case of charged fluid spheres. These solutions are matched at the boundary with the Reissner-Nordström solution. © 1993 Kluwer Academic Publishers.